Addressing the oral healthcare needs of special needs children: pediatric nurses' self‐perceived effectiveness. (19th June 2013) - Parish, Carrigan L.; Singer, Richard; Abel, Stephen; Metsch, Lisa R.
ABSTRACT Objectives To examine the oral health knowledge and practices of pediatric nurses who coordinate healthcare services for special needs children and to identify those factors that influenced their perceived effectiveness in managing their patients' oral health needs. Methods Self‐reported data were collected from 376 nurses employed at Children's Medical Services who responded to an online survey. Likert scale scores were used to specifically assess the nurses' perceived effectiveness in addressing the oral health needs of special needs children. Results Characteristics significantly associated with special needs pediatric nurses who described themselves as "effective or very effective" included: the self‐perception of being very knowledgeable about basic oral health, receiving four or more hours of continuing education training, and securing dental appointments for the majority of their pediatric special needs patients with minimal waiting times. Conclusion Findings reveal that oral health knowledge significantly influenced nurses' perceived effectiveness in addressing the oral health needs of special needs children, as well as their ability to secure timely dental appointments. These results support the need to incorporate oral health education into nursing curricula and expand upon the dental workforce available and willing to treat disabled patients.